Blood–brain barrier leakage increases with small vessel disease in acute ischemic stroke. (21st November 2017) - Arba, Francesco; Leigh, Richard; Inzitari, Domenico; Warach, Steven J.; Luby, Marie; Lees, Kennedy R.
Abstract : Objective: In patients with acute ischemic stroke, we aimed to investigate the relation between preexisting small vessel disease (SVD) and the amount of blood–brain barrier (BBB) leakage in ischemic and nonischemic area before IV thrombolysis. Methods: We retrospectively accessed anonymous patient-level data from the Stroke Imaging Repository and the Virtual International Stroke Trials Archive resources and included patients treated with IV thrombolysis with pretreatment MRI. We rated SVD features using validated qualitative magnetic resonance (MR) scales. Leakage of BBB was assessed with postprocessing of perfusion-weighted images. We evaluated associations between SVD features (individually and summed in a global SVD score) and BBB leakage using linear regression analysis, adjusting for major clinical confounders. Results: A total of 212 patients, mean age (±SD) 69.5 years (±16.1), 102 (48%) male, had available MR before IV thrombolysis. Evidence of BBB leakage was present in 175 (80%) and 205 (94%) patients in the ischemic and nonischemic area, respectively. Lacunar infarcts (β = 0.17, p = 0.042) were associated with BBB leakage in the ischemic area, and brain atrophy was associated with BBB leakage in both ischemic (β = 0.20, p = 0.026) and nonischemic (β = 0.27, p = 0.001) areas. Increasing SVD grade was independently associated with BBB leakage in both ischemic (β = 0.26, p = 0.007) and nonischemic (β = 0.27, p = 0.003) area. Conclusions: Global SVD burden is associated with increased BBB leakage in both acutely ischemic and nonischemic area. Our results support that SVD score has construct validity, and confirm a relation between SVD and BBB disruption also in patients with acute stroke.